Defining outcomes of patients with clinical stage I small cell lung cancer upstaged at surgery. (January 2017) - Thomas, Daniel C.; Arnold, Brian N.; Rosen, Joshua E.; Salazar, Michelle C.; Blasberg, Justin D.; Detterbeck, Frank C.; Boffa, Daniel J.; Kim, Anthony W.
Highlights: Pathologic upstaging is common after surgical resection of stage I SCLC. Pathologic upstaging is associated with inferior survival after resection. Adjuvant therapy improved survival of patients upstaged for nodal disease. These data support use of adjuvant therapy for pathologically upstaged SCLC. Abstract: Background: A proportion of patients with clinical stage I small cell lung cancer (SCLC) will be upstaged following surgical resection. The existing data regarding the management of upstaged SCLC patients and guidelines for their treatment remains sparse. The primary objective was to describe the impact of pathologic upstaging following surgical resection. Methods: The National Cancer Database was queried for patients with clinical stage I SCLC (cT1-2a, N0, M0) who underwent resection with curative intent followed by adjuvant therapy, excluding patients who underwent surgery alone. Clinical and pathologic T, N, and M staging were compared to identify patients that were upstaged. Results: Four-hundred and seventy-seven patients were identified with clinical stage I SCLC. Pathologic upstaging occurred in 25% (117). Of those upstaged, 30% (35) were due to a higher pathologic T descriptor and 81% (95) were due to the presence of nodal disease. Overall 5-year survival was significantly worse for upstaged patients compared with those patients who remained a pathologically stage I (36% vs 52%, p < 0.001). Among patients with positive lymph node involvement, adjuvant chemotherapy and radiation therapy was associated a significantly improved 5-year survival compared to adjuvant chemotherapy alone (20% vs 55%, respectively, p < 0.01). The use of adjuvant chemotherapy and radiation therapy in patients with nodal disease after surgical resection was an independent predictor of improved survival (HR 0.36, 95% CI 0.18–0.73, p < 0.01). Conclusions: Pathologic upstaging is common after surgical resection of stage I SCLC, and is associated with significantly inferior survival. These data provide evidence that recommend the use of adjuvant chemotherapy and radiation therapy in the setting of nodal upstaging after resection of clinical stage I SCLC patients.